COVID-19 infection and later risk of sickness absence by socioeconomic status: a cohort study - Matti Joensuu; Johanna Kausto; Jaakko Airaksinen; Tuula Oksanen; Jussi Vahtera; Mika Kivimäki; Jenni Ervasti (BMC Public Health)
Abstract Background The COVID-19 pandemic was a significant health risk and resulted in increased sickness absence during the pandemic. This study examines whether a history of COVID-19 infection is associated with a higher risk of subsequent sickness absence. Methods In this prospective cohort study, 32,124 public sector employees responded to a survey on COVID-19 infection and lifestyle factors in 2020 and were linked to sickness absence records before (2019) and after (2021–2022) the survey. Study outcome was annual sickness absence defined as the total number of sickness absence days and the number of short sickness absence spells (< 10 days) and long sickness absence spells (10–365 days). We used negative binomial regression adjusting for sex, age, employment characteristics, body mass index, health behaviors in 2020 and sickness absence in 2019. We examined differences in sickness absence between socioeconomic statuses (SES), measured by occupational titles from employers’ records. Results A self-reported COVID-19 infection in 2020 was associated with higher subsequent risk of sickness absence in 2021: Adjusted Incidence Rate Ratio (IRR) compared to those not reporting COVID-19 was 1.23, 95% confidence interval (CI) 1.10–1.37 for sickness absence days, 1.29, 1.20–1.38 for short sickness absence spells and 1.20, 1.04–1.37 for long spells. The association was strongest in employees with intermediate SES: 1.45, 1.20–1.77 days, 1.42, 1.26–1.61 short spells, and 1.30, 1.03–1.64 long spells. For employees with low and high SES, an association was observed only for short spells. Conclusions Employees who reported contracting first-wave COVID-19 infection had higher rates of sickness absence in the following year. This excess risk was most consistently observed in employees with intermediate socioeconomic status (e.g. office workers, registered nurses, and social workers).